EVALUASI SISTEM INFORMASI RAWAT JALAN PADA RUMAH SAKIT MENGGUNAKAN FRAMEWORK COBIT 4.1 - Madiyono Madiyono; Sri Siswanti; Sri Harjanto (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2019)
Brayat Minulya Hospital is a privately owned hospital engaged in health care services for the general public. In the patient service process, the hospital has used an information system called Graphasoft which is used for outpatient and inpatient services. Currently the outpatient information system (SiRajal) has been running computerized, where all the processes associated with the patient have been input into the system, but there are still obstacles with the slow performance of patient registration on SiRajal and not yet the implementation of monitoring and evaluation process on SiRajal so it is not known whether the system runs in accordance with the hospital's business plan. From these problems, it is necessary to evaluate the outpatient information system using a method that refers to the IT Governance standard that is using the COBIT framework (Control Objectives For Information And Related Technology). The COBIT framework used is version 4.1, with the domain focus of ME (Monitor and Evaluate) on the ME1 subdomain (Monitor and Evaluate IT Performance). Acquisition of data to be processed taken by interview method, questionnaire, analysis of evaluation framework COBIT 4.1. The results of data analysis showed that obtained the calculation of the mean value of maturity of CO ME1 that is at maturity level 2 (Repeatable but Intuitive). still far below the expectations of management. For that recommendation of improvement of findings of the analysis of the results of the Institution is expected to make the work program appropriately, effectively and efficiently to set standards, policies, and procedures on monitoring IT performance optimally, so that SiRajal performance can run smoothly in the future.Keywords : Information System, Framework COBIT 4.1, Maturity Level